GREEN CENTRAL BANKING: A NEW ROLE FOR THE CENTRAL BANKS IN THE FINANCIAL SYSTEM - Omer Faruk Tekdogan (Journal of Central Banking Law and Institutions, 2023)
The financial sector has a key role to play in the transition to a more sustainable and low-carbon economy. Being major actors in the financial system, central banks can exert influence to encourage the adoption of green finance and reduce risks associated with climate change. A novel idea called "green central banking" aims to give central banks' operations, regulations, and goals more sustainability-related thought. This study explores the concept of "green central banking," which is just starting to gain traction, as well as potential central bank responsibilities and tasks in the field of sustainable finance. This study also emphasizes the difficulties and dangers of implementing green central banking, including the possible conflicts between financial stability and environmental goals. Also, the article provides a comparative examination of the methods used by central banks as it looks at the state of green central banking in various parts of the world. Ultimately, this study promotes central banks to take a proactive stance in the transition to a greener and more resilient financial system and believes that green central banking can be a critical tool for accomplishing sustainable development goals.